2015
DOI: 10.1111/cpf.12242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake on left and right ventricular systolic tissue Doppler measurements

Abstract: Systolic tissue Doppler measurements (s') have been used to measure the velocity in myocardial motion and are a valuable tool for evaluating the systolic function of the left and right ventricles. Digestion of food is known to significantly alter hemodynamics and may therefore affect s'. The effect of food intake on s' parameters has not yet been studied. We assessed whether s' is affected by food intake. Nineteen healthy subjects aged 26·2 ± 4·2 years were investigated. s' was measured with pulsed tissue Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
3
9
1
Order By: Relevance
“…Although there was a small decrease in ejection time, the main alteration leading to the significant decrease in MPI after eating is the decrease in ICT + IRT. In comparison to our previous findings [1416] the change in MPI is larger than the changes seen for diastolic parameters, and of the same magnitude as several systolic changes. The exact mechanisms behind the findings in the present investigation are hard to define.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although there was a small decrease in ejection time, the main alteration leading to the significant decrease in MPI after eating is the decrease in ICT + IRT. In comparison to our previous findings [1416] the change in MPI is larger than the changes seen for diastolic parameters, and of the same magnitude as several systolic changes. The exact mechanisms behind the findings in the present investigation are hard to define.…”
Section: Discussioncontrasting
confidence: 90%
“…We have previously reported data from our cohort on the effect of food intake on systolic and diastolic function [1416]. The purpose of the present study is to evaluate the hypothesis that food intake, in healthy volunteers, may have an effect on myocardial performance index, as it is considered a reflection of the total left ventricular function.…”
Section: Introductionmentioning
confidence: 99%
“…There is a continuous search for novel biomarkers that could improve the assessment in neurological diseases (Lind et al., ; Lind, Emami Khoonsari et al., ; Lind, Wu et al., ; Miclescu, Svahn, & Gordh, ; Moen et al., ). Digestion of food is known to have significant hemodynamic and metabolic effects (Dencker, Björgell, & Hlebowicz, ; Dieden, Gårdinger, Bjorgell, Hlebowicz, & Dencker, ; Gårdinger, Bjorgell, Hlebowicz, & Dencker, ; Hlebowicz, Lindstedt‐Ingemansson, Björgell, & Dencker, ; Hlebowicz, Lindstedt‐Ingemansson, Björgell, & Dencker, ; Quatela, Callister, Patterson, & MacDonald‐Wicks, ; Stensel, ), and may therefore affect different biomarkers. It is relevant from a practical point of view to investigate if these biomarkers are affected by food intake, as it would affect sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Digestion of food is known to alter hemodynamics, [5][6][7] and we have previously shown that both systolic and diastolic functions are affected significantly when comparing echocardiographic exams during fasting and after a meal in a young population. [8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically.…”
Section: Introductionmentioning
confidence: 93%
“…[8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically. [12][13][14][15][16] Hence, senior people are an important target group in cardiovascular studies.…”
Section: Introductionmentioning
confidence: 93%